Role of Remittances on Rural Poverty in Nepal-Evidence from Cross-Section Data - Byanjanakar, Rohan; Shakha, Mira (NRB Economic Review, 2021)
This paper attempts to determine the impact of remittance on rural poverty in Nepal using the microdata set of household risk and vulnerability survey 2016 – 2018. The cross-sectional analysis has been carried out using a dataset of 2018 with 5,645 households across 50 districts of Nepal. The logit regression model has been used to determine the relationship between poverty and remittances. About 38 percent of rural households received remittances in 2018. About 65 percent of households headed by females received remittance compared to 30 percent of households headed by male counterparts. About 41 percent, 31 percent, and 32 percent of households living in the Hilly region, Terai, and Himalayan region respectively received remittance in 2018. About 1 in every 5 households in rural Nepal is poor. The probability of households falling into poverty reduces by 4.8 percent with a one percent rise in household assets. Remittance receiving households are 2.3 percent less likely to get caught in poverty as compared to remittance non-receiving households. The probability of households plunging into poverty decreases by about 1.1 percent with every 10 percent increase in remittance inflows to households.